Literature on Starch Nanoparticles Used in Drug Delivery Systems: A Review - Bahmani, Kavita; Rani, Nisham; Malik, Jyoti; Devi, Meena; Tushir, Shiva; Soni, Yash; Devi, Sunita (Current Physical Chemistry, 2025)
Particle size has become a more prominent topic in multidisciplinary research in recent years, which aids in examining the relationship between the microscopic and macroscopic characteristics of different materials. Generally, acid/enzymatic hydrolysis, gamma irradiation, simple nanoprecipitation, ultra-sonication, and homogenization treatments are used to create starch nanoparticles. After starch is converted into nanoparticles, various features are impacted, including size distribution, morphological, rheological, and amylose content. It has been shown that starch nanoparticles are superior to natural starches; therefore, they have a wide range of applications as fillers, binding agents, and texture modifiers in various food products, as well as in the production of biocomposite films with improved barrier properties. The principal applications for starch nanoparticles include medication administration, nanoemulsions, and nano-starch-based composite films. There is a dearth of research on the effects of starch nanoparticle production on different native starch characteristics. In order to maximize the use of starch nanoparticles in food and non-food applications, this study thoroughly reviews all factors pertaining to different starch characteristics and their nanoparticles. Particular attention is paid to the abstract review of the literature on starch, which gives a clear idea of the relevance of this study.
Keywords: modification of starch